2020
DOI: 10.1016/j.jare.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of long noncoding RNA HIF1A-AS2 confers protection against atherosclerosis via ATF2 downregulation

Abstract: Graphical abstract The map illustrating mechanisms associated with lncRNA HIF1A-AS2-mediated inflammation in the atherosclerosis. LncRNA HIF1A-AS2 forms a complex with USF1, which is recruited into the ATF2 promoter to elevate ATF2 expression, thus promoting the development of atherosclerotic inflammation. Meanwhile, downregulation of lncRNA HIF1A-AS2 decreases the expression of ATF2 by reducing the binding of USF1 to the ATF2 promoter regions, thereby inhibiting atherosclerotic inflammation, as ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…ATF2 has been reported to be involved in the regulation of inflammation in atherosclerosis. For example, the downregulation of long non-coding RNA HIF1A antisense RNA 2 has been shown to inhibit atherosclerotic inflammation by suppressing ATF2 [ 33 ]. Another study showed that ATF2 regulates anti-inflammatory activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATF2 has been reported to be involved in the regulation of inflammation in atherosclerosis. For example, the downregulation of long non-coding RNA HIF1A antisense RNA 2 has been shown to inhibit atherosclerotic inflammation by suppressing ATF2 [ 33 ]. Another study showed that ATF2 regulates anti-inflammatory activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of USF1 expression increases the expression of VEGF ( 55 ). In addition, Li et al proved that inhibiting the expression of USF1 significantly reduces the expression of inflammatory factors such as IL-1β, TNF-α, and IL-6, thereby alleviating atherosclerotic inflammatory responses ( 56 ). Therefore, USF1 may be involved in atherosclerosis by regulating the expression of IL-1β, VEGF, TNF-α, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that ATF2 is highly correlated with neutrophils and endothelial cells, suggesting that leukocyte-endothelial adhesion also appears in the IDD immune response, reflecting a characteristic of the changes in the IDD immune microenvironment. ATF2 mainly participates in the inflammatory response through the JNK and p38 MAP kinase pathways [ 47 ]. The low expression of ATF2 can lead to the excessive activation of the immune system and the massive invasion of T cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%